ANALISIS EFEKTIVITAS BIAYA PENGOBATAN DEMAM TIFOID PADA ANAK MENGGUNAKAN ANTIBIOTIK KLORAMFENIKOL DAN SEFIKSIM (STUDI OBSERVASI ANALITIK DI RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG. PERIODE JANUARI – DESEMBER 2015 - Rosyid, Abdur; Timur, Willi Wahyu; nafirin, Athikan (Media Farmasi Indonesia, 2017)
ABSTRACTBackground: Typhoid fever is an acute infectious disease of the gastrointestinal tract caused by Salmonella Typhi. This disease ranks third among the most prevalent diseases pattern 10 inpatients at the hospital in 2006 with the number of 72 804 patients (3:26%) (MOH, 2007). Chloramphenicol antibiotic treatment is very cost effective for the treatment of typhoid fever in children and for antibiotics cefixime proved to be good and effective. This study aims to determine the cost-effectiveness of treatment of typhoid fever in children in the Islamic Hospital Sultan Agung Semarang period from January to December, 2015Metod : This type of research is analytic observational retrospective approach. The research sample is taken from a medical record inpatient Islamic Hospital Sultan Agung Semarang period from January to December 2015 have met the inclusion criteria, data analysis using ACER value calculation is the total cost of treatment is divided by the length of stay.Result :The results showed that 53 samples obtained in room B. Nisa '2 of the 31 medical records of patients with a diagnosis of typhoid fever that using antibiotics chloramphenicol and cefixime, and room B. Nisa' 3 at 22 medical records of patients with a diagnosis of typhoid fever that using antibiotics chloramphenicol and cefiximeConclusion :Treatment of typhoid fever in children with antibiotics chloramphenicol is more cost effective than the antibiotic cefixime therapy group. Antibiotic chloramphenicol in Space Baitun Nisa '2 have the cost effectiveness of treatment with ACER value of USD 376 775 / day and for room Baitun Nisa' 3 Rp 296 980 / day